Mesoscale oceanographic features drive divergent patterns in connectivity for co‐occurring estuarine portunid crabs. (7th September 2022) - Hewitt, Daniel E.; Schilling, Hayden T.; Hanamseth, Roshan; Everett, Jason D.; Li, Junde; Roughan, Moninya; Johnson, Daniel D.; Suthers, Iain M.; Taylor, Matthew D.
Abstract: Larval dispersal and connectivity have important implications for fisheries management, especially for species with life cycles influenced by ocean boundary currents. Giant Mud Crab ( Scylla serrata ) and Blue Swimmer Crab ( Portunus armatus ) are two estuarine portunid crabs (Family: Portunidae) that support significant commercial and recreational harvest in eastern Australia. Giant Mud Crab migrate to coastal waters to spawn, and while Blue Swimmer Crab spawn primarily within estuaries they occasionally migrate to coastal waters to spawn, followed by larval dispersal in the East Australian Current (EAC). Here, we coupled a high‐resolution oceanographic model with a Lagrangian particle tracking framework to simulate larval dispersal and determine the extent of population connectivity in this region. Our simulations indicate broad‐scale connectivity ( 40–400 km), characterised by high inter‐estuary connectivity. Overall, our results suggest a north‐to‐south source‐sink structure for both species, with contributions of particles from the north ranging from 51% to 99%. Recruitment to a given estuary is dependent on the proximity of mesoscale oceanographic features of the EAC. Most notably, the EAC separation acts as a barrier to recruitment between spawning and settlement to the north/south of this region. This significantly limits interjurisdictional connectivity for these species, especially Blue Swimmer Crab, likely due to a shorter pelagic larval duration than Giant Mud Crab. Our results provide evidence to inform the assessment and management of these species.